2006
DOI: 10.1021/bi0612521
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis and Assembly of the HIV-1 Gp41 Amino-Terminal Fusion Peptide and the Pretransmembrane Amphipathic-At-Interface Sequence

Abstract: The amino-terminal region within the HIV-1 gp41 aromatic-rich pretransmembrane domain is an amphipathic-at-interface sequence (AIS). AIS is highly conserved between different viral strains and isolates and recognized by the broadly neutralizing 2F5 antibody. The atomic structure of the native Fab2F5-bound AIS appears to involve a nonhelical extended region and a beta-turn structure. We previously described how an immunogenic complex forms, based on the stereospecific interactions between AIS and the gp41 amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 56 publications
(103 reference statements)
2
56
0
Order By: Relevance
“…Other authors had shown an interaction between MPER and FPPR during infection [18][19][20][21][22]. These findings suggested that the interaction between the MPER and the FPPR during infection may generate a conformation able to induce 2F5/4E10-like neutralising antibodies.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Other authors had shown an interaction between MPER and FPPR during infection [18][19][20][21][22]. These findings suggested that the interaction between the MPER and the FPPR during infection may generate a conformation able to induce 2F5/4E10-like neutralising antibodies.…”
Section: Discussionmentioning
confidence: 83%
“…There may be several reasons for the failure of many of the attempts to induce 2F5/4E10-like neutralising antibodies including our new approach: First, although it has been shown, that peptides derived from the FPPR increase the binding of mAb 2F5 to its epitope in the MPER/ E2 domain [14] and there is an interaction between MPER and FFPPR [18][19][20][21][22], it is still unknown whether this interaction is also required for the induction of 2F5/4E10-like broadly neutralising antibodies. Second, it remains unclear, whether the DNA immunisation generated the correct membrane associated context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, this pre-TM region may act in conjunction with other sequences in the gp41 ectodomain to maintain the native and fusion states of the Env. Lorizate et al showed that the fusion peptide and pre-TM sequence can coassemble into a defined complex that acts as a prefusion clasp to restrict fusion peptide-mediated fusion (39,40). The Trp-rich membrane-proximal region and the N-terminal fusion peptide-proximal polar segment were recently shown to act synergistically to form a fusion-competent prefusion gp120-gp41 complex and stabilize the membrane-interactive end of the trimeric hairpin fusion core (2).…”
Section: Discussionmentioning
confidence: 99%
“…Hydropathy plots calculated according to the Wimley-White (WW) scale (81) actually revealed a fully hydrophobic-at-interface sequence within gp41 MPER, previously termed the pretransmembrane domain (PreTM) (39,50,59,70,71). Thus, the gp41 region spanning the 2F5 and 4E10 epitopes has a specific affinity for the membrane interface, the lipid bilayer region between the high-polarity water phase and the low-polarity hydrocarbon core (79).Subsequent development of WW scale applications, including the simultaneous computation of interfacial affinity and hydrophobic moments (38,58), revealed that the MPER was segmented into two subdomains, a phenomenon that was pro-* Corresponding author. Mailing address:…”
mentioning
confidence: 99%